On the asymptotic behavior of effective QED at finite temperature - Tomazelli, J. L.; Costa, L. C. (Springer, 2003)
The aim of this paper is to study finite temperature effects in effective quantum electrodynamics using Weisskopf's zero-point energy method in the context of thermo, field dynamics. After a general calculation for a weak magnetic field at fixed T, the asymptotic behavior of the Euler-Kockel-Heisenberg Lagrangian density is investigated focusing on the regularization requirements in the high temperature limit. In scalar QED the same problem is also discussed.